How do I incorporate red cell genotyping to improve chronic transfusion therapy?. Issue 1 (23rd November 2019) - Van Buren, Nancy L.; Gorlin, Jed B.; Corby, Susan M.; Cassidy, Sandra; FritchLilla, Stephanie; Nelson, Stephen C.; Westhoff, Connie M.
Abstract : BACKGROUND: Children with transfusion dependent anemia, such as sickle cell disease (SCD) and thalassemia, are at an increased risk for developing red blood cell (RBC) alloantibodies due to their lifelong need for transfusion therapy. With the advent of genotyping, extended RBC antigen typing can be incorporated into chronic transfusion therapy programs (CTTPs) to improve patient care and provide antigen matched blood for this population of patients. STUDY DESIGN AND METHODS: The hospital, blood center (BC), and hematology clinic caring for children requiring long‐term transfusion support developed a CTTP. Genotyping was performed at entry to determine patient RBC antigen type. Limited versus extended antigen matching of transfusions was provided based on known RBC antibodies. RESULTS: Fifty patients with the following disorders were enrolled: 20 with SCD, 23 with thalassemia, and 7 with other disorders. At enrollment, nine (18%) had RBC alloantibodies, including six (30%) of patients with SCD and three (13%) with thalassemia. Two children developed antibodies after enrollment; one warm autoantibody following limited "CEK" matched RBCs and one patient with a hemizygous variant RHD allele developed anti‐D. Six (30%) patients with SCD had variant RHCE alleles; two had homozygous variant alleles and four had a variant present along with a wild type allele. CONCLUSION: We demonstrate how a CTTP can be developed in a community hospital through collaboration with the blood supplier, hospital, and clinical care team. A model of incorporating RBC genotyping informs risk for alloimmunization and allows consideration of transfusion strategy for providing prophylactic antigen matched blood.